Educating Science Teachers in Earth Science Teaching: The Earth Science Education Unit Initiative in England and Wales, and its Transfer to Scotland - King, Chris; Lydon, Susannah (Journal of Geography Education, 2007)
The Earth Science Education Unit (ESEU) presents professional development workshops to secondary (high school) teachers and trainee (pre-service) science teachers in England and Wales and to upper primary (elementary) teachers in Scotland. The workshops enhance the background Earth science knowledge of the teachers, through showcasing a variety of engaging Earth science activities which enhance effective use of practical activities in science whilst developing critical thinking and investigational skills in pupils. Research into the impact of the workshops in England and Wales has shown that the activities are widely taken up in the schools visited and that most schools subsequently change their long-term science planning to include ESEU activities. A key element is the increase in confidence and enthusiasm of the staff involved. Word frequency analysis of written feedback has shown that trainee teachers referred to evidence and theory more frequently than practising teachers, while practising teachers used terms relating to positive affective responses more frequently than trainees. These differences may relate to the changing CPD needs of teachers at different career stages. ESEU has successfully transferred its approach to the quite different educational environment of Scotland, as shown by the numbers of teachers undertaking the workshops and their very positive responses. As a result, key factors have been identified that need to be present in order to successfully transfer the ESEU approach to other countries. An international survey has identified developing countries where these factors are present, as a precursor to submitting a bid for International Year of Planet Earth funding, to pilot the ESEU approach in these countries.